Dampak Pola Asuh Orang Tua Dirumah terhadap Penggunaan Gadget Anak Usia Dini - Ulfadhilah, Khairunnisa Ulfadhilah; DwiNurkhafifah, Salsabila (Jurnal Pendidikan Educandum, 2026)
Parenting at home has a significant impact on gadget use in early childhood, which can be traced through a narrative research approach. This method allows the collection of stories and experiences of parents and children regarding their interactions with technology. In this study, in PAUD An-Nur, the narrative obtained shows that democratic parenting, which prioritizes open communication, can be useful in guiding children to use gadgets wisely. On the contrary, authoritarian parenting often creates tension, triggering children to hide in excessive use of gadgets. In addition, parent stories show that the presence of parents in guiding the use of gadgets, such as setting screen time and choosing educational content, has a positive effect on children's cognitive and social development. By delving into this experience, this study reveals that emotional support and active involvement of parents in digital activities are able to foster healthy habits in the use of technology. This creates a higher awareness in children about limits and responsibilities, as well as the impact of technology on their mental and physical health. Furthermore, the results of the study highlight the importance of training for parents on the healthy use of gadgets, so that they can be good role models. Through true stories, this research provides insight into how parenting styles not only affect children's behavior with gadgets, but also help build the foundation for their social and emotional development in this digital age. Thus, the narrative approach provides an in-depth perspective on the complexity of the relationship between parenting and gadget use, which has implications for policy recommendations and practices in the field of early childhood education.